Ultramicronized N-Palmitoylethanolamine Supplementation for Long-Lasting, Low-Dosed Morphine Antinociception - Di Cesare Mannelli, Lorenzo; Micheli, Laura; Lucarini, Elena; Ghelardini, Carla (Frontiers in Pharmacology, 2018)
The facilitation of opioid medication is eliciting a nemetic problem since increasing overdose deaths involve prescription of opioid pain relievers. Chronic painful diseases require higher doses of opioids, progressively with the development of tolerance to the antinociceptive effect. Novel strategies for the maintenance of low dosed opioid effectiveness are necessary o relieve pain and decrease abuse, overdose and side effects. N-Palmitoylethanolamine (PEA) is an endogenous compound able to preserve the homeostasis of the nervous system and to delay the development of morphine tolerance. In the present study, a preemptive and continuative treatment with PEA (30 mg/kg, daily, per os) enhanced the acute antinociceptive efficacy of morphine (10 mg/kg subcutaneously) in rats and prolonged the responsiveness to the natural opioid. Moreover, PEA-treated animals had a more rapid recovery from tolerance. Four opioid free days were enough to regain sensitivity to morphine whereas control animals needed 31 days for full recovery of tolerance. Characteristically, PEA acquired per se antinociceptive properties in tolerant animals, suggesting the possibility of an integrated morphine/PEA treatment protocol. To maintain a significant analgesia, morphine dose had to be increased from 5 up to 100 mg/kg over 17 days of daily treatment. The same pain threshold increase was achieved in animals using preemptive PEA (30 mg/kg, daily) joined to a combinatorial acute treatment with morphine (5 – 20 mg/kg s.c.) and PEA (30 – 120 mg/kg, p.o.). Representatively, on day 17, the magnitude of analgesia induced by 100 mg/kg morphine was obtained by combining 13 mg/kg of morphine with 120 mg/kg of PEA. PEA strengthens the efficacy and potency of morphine analgesia, allowing prolonged and effective pain relief with low doses. PEA is suggested in association with morphine for chronic pain therapies distinguished by low risk of side effects.